Burlesque Works of Tom Tavares - Manuscript 736 BPMP (Global Journal of Human-Social Science, 2013)
Son of a period of profound transformations Tom Tavares 1570-1634 is part of a baroque spirit marked by the unveiling of the words and by the satire s poisonous and unmeasured guillotine In a society marred by hypocrisy and the worldly frivolities burlesque satire comes as a regenerator blow giving rise not only to an irreverent laugh often in complicity but also as a releasing factor by a world steeped in misrepresented values
Keywords: poetry; baroque; satire